Effect of Price, Health Consciousness, Food-Safety Concern, Prestige, Affordances, Visibility, Trust, and Customer Satisfaction on Repurchase Intention Online Food Delivery (OFD) To Customers in Jakarta - Teh Harianto; Margaretha Pink Berlianto (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The development of the times and technology continues to change as well as the competition that occurs now this has changed corner look company in Fulfill market. The demand for change is a must because only those who are ready to change and innovate survive. Companies must always anticipate happening something change because with change there will be an opportunity for the new and the old will be left behind. By knowing the effect of Price, Health consciousness, Food-safety concern, Prestige, Affordances, and Visibility on repurchase intention online food delivery (OFD) which is mediated by customer satisfaction and trust, it is hoped that this research can provide input that can be used by merchants so that the factors that influence purchase intention can be a focus for improvement. According to Sugiyono (2016), the research method is a scientific way to obtain data with certain goals and uses. In this study, the research method used by the author is quantitative. According to Sugiyono (2016), quantitative research can be defined as a research method based on the philosophy of positivism, used to examine certain populations or samples, collect data with research instruments, analyze data quantitatively/statistically, and aim to test predetermined hypotheses. The results of this study provide support for previous research on customer satisfaction acting as a stronger mediation than trust. This study was conducted to determine the effect of price, health consciousness, food-safety concern, prestige, affordances, and visibility on repurchase intention. online food delivery (OFD) mediated by customer satisfaction and trust in customers in Jakarta.